Clinical overview and practical considerations for optimizing romiplostim therapy in patients with immune thrombocytopenia. (September 2021) - Kuter, David J.; Tarantino, Michael D.; Lawrence, Tatiana
Abstract: The fundamental treatment goal for patients with immune thrombocytopenia (ITP) is reduced or ameliorated bleeding. Although various treatment options exist for the management of ITP, recent advances have led to the approval of three thrombopoietin receptor agonists (TPO-RAs; romiplostim, eltrombopag, and avatrombopag) in the United States and European Union. Current treatment guidelines for ITP indicate that medical therapy is preferred over surgical therapy and support the use of TPO-RAs as early as 3 months after disease onset. More recent data are available on the use of romiplostim in patients who have had ITP for <1 year, and romiplostim is now indicated for the treatment of adults who have not responded adequately to initial treatment, as well as children aged ≥1 year who have had ITP for ≥6 months. Here we review the role of romiplostim in the management of ITP, with a focus on efficacy and safety data, emerging data on early use (beginning within 3 months of disease onset) and treatment-free remission, and practical considerations for optimal management of ITP. Highlights: Updated ITP guidelines include early (disease duration <1 year) use of TPO receptor agonists after initial steroid failure. Treatment-free remissions occur in more than one-third of recently diagnosed adults within one year ofstarting romiplostim. Romiplostim provides platelet response rates of ~80%–90% in early (ITP present for <6 months) and chronic ITP. Long-term safety has been established with >10 years of use. Romiplostin use should be carefully considered in patients with thrombotic risk factors.